HUBUNGAN DUKUNGAN KELUARGA TERHADAP TINGKAT STRES PASIEN DIABETES MELITUS DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Christmasni Grace Yosephine; Veny " Elita; Nurul " Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract This study aims to determine the relationship between family support and the level of stress patients with type 2 diabetes mellitus. This research method using descriptive correlation design with the cross-sectional approach. The study is conducted at Arifin Achmad General Hospital to 42 respondents with type 2 diabetes mellitus, taken by accidental sampling technique. Measuring instrument uses family supports questionnaire to measure the level of family support and Depression Anxiety Stress Scale questionnaire to measure the level of stress. The analytical method used is the analysis of univariate and bivariate Kolmogorov-Smirnov test. The results show that there are a relationship between family support and stress level of patients with type 2 diabetes mellitus with p = 0.000 <α = 0.05. The conclusion of this study is that there a significant relationship between family support and the level of stress of patient with diabetes mellitus type 2. Based on the results of this study, the family of patients with type 2 diabetes mellitus are expected to provide family support to minimize stress levels, because of low family support can increase stress levels of patients with diabetes mellitus type 2. Keyword : Type 2 diabetes mellitus, family support, stress